Structural Analysis - Bauchau, O.A.; Craig, J.I. (Springer, 2009)
Engineered structures are almost as old as human civilization and undoubtedly began with rudimentary tools and the first dwellings outside caves. Great progress has been made over thousands of years, and our world is now filled with engineered strucfrom fragile human-powered aircraft to sleek jets and thundering rockets are, in our opinion, among the most challenging and creative examples of these efforts. The study of mechanics and structural analysis has been an important area of engineering over the past 300 years, and some of the greatest minds have contributed to its development. Newton formulated the most basic principles of equilibrium in the 17th century, but fundamental contributions have continued well into the 20th century. Today, structural analysis is generally considered to be a mature field with well-established principles and practical tools for analysis and design. A key reason for this is, without doubt, the emergence of the finite element method and its widespread application in all areas of structural engineering. As a result, much of today’s emphasis in the field is no longer on structural analysis, but instead is on the use of new materials and design synthesis. The field of aerospace structural analysis began with the first attempts to build flying machines, but even today, it is a much smaller and narrower field treated in far fewer textbooks as compared to the fields of structural analysis in civil and mechanical engineering. Engineering students have access to several excellent texts such as those by Donaldson [1] and Megson [2], but many other notable textbooks are now out of print.
With Applications to Aerospace Structures